Penyediaan Bibit Tanaman Hias Oleh Mahasiswa KKN Untuk Program Penghijaun Kampus - Lolita Endang Susilowati; Hidayatul Fathi; Ashari Kautsar; Nurul Fitriani (Universitas Mataram, 2022)
Ornamental plant nursery is one form of activity in the thematic KKN-Green Campus. This activity aims to provide plant seeds that are ready to be planted in campus gardens. The nursery activity begins with enriching students' knowledge of plant propagation techniques. The theory of plant propagation is given in class, then followed by nursery practice. The nursery is carried out in the campus environment, starting with the construction of a paranet house located in the Aquaculture Study Program building, Faculty of Agriculture, University of Mataram, then preparing seedling media and planting equipment. There are five types of seeds provided, namely sunflower seeds, marigolds, puring, nine o'clock flowers and Miana tricolor, with a total of 300, 300, 25 80 and 15 seeds, respectively. The propagation of sunflower and marigold plants was carried out generatively and puring, nine o'clock flowers and Miana tricolor flowers were propagated vegetatively. This activity also succeeded in building students' hard skills in plant nurseries, as shown by their success in germinating plants, which on average reached 100% of the number of prepared seeds that were ready to be planted